2017
DOI: 10.1111/bju.13839
|View full text |Cite
|
Sign up to set email alerts
|

Mini PCNL for renal calculi: does size matter?

Abstract: ObjectiveTo evaluate the minimally invasive percutaneous nephrolithotomy (MIP) system for renal calculi. Patients and MethodsConsecutive patients undergoing mini-percutaneous nephrolithotomy (mPCNL) procedures with the MIP system were enrolled. Patient position, American Society of Anesthesiologists classification, puncture location, stone clearance, postoperative drainage and complications were recorded, and features unique to MIP were noted. ResultsIn all, 30 patients underwent 32 mPCNL procedures. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
1
15
0
2
Order By: Relevance
“…In 2012, Abdelhafez et al reported on 83 patients treated with the mini-PCNL, in which the upper calyx of kidney puncture accounted for 4.8%, the middle calyx of kidney puncture 10.8%, and the rest was the lower calyx of kidney [3]. Hennessey et al studied 32 cases treated using the mini-PCNL, of which 24 cases (75%) were punctured at the lower calyx of kidney, 12.5% at the middle calyx of kidney, and 12.5% the upper calyx of kidney [5]. For simple stones, using the calyx of kidney, renal pelvis puncture to directly approach the stones is the best way to the stone fragmentation and to limit damage and complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2012, Abdelhafez et al reported on 83 patients treated with the mini-PCNL, in which the upper calyx of kidney puncture accounted for 4.8%, the middle calyx of kidney puncture 10.8%, and the rest was the lower calyx of kidney [3]. Hennessey et al studied 32 cases treated using the mini-PCNL, of which 24 cases (75%) were punctured at the lower calyx of kidney, 12.5% at the middle calyx of kidney, and 12.5% the upper calyx of kidney [5]. For simple stones, using the calyx of kidney, renal pelvis puncture to directly approach the stones is the best way to the stone fragmentation and to limit damage and complications.…”
Section: Discussionmentioning
confidence: 99%
“…Among 642 patients who were successfully punctured, with a tunnel created and the kidney approached, the mean operative time was 49.3 (37-90) min, and the longest was 90 min, recorded in the case with staghorn stones (Table 2). According to Hennessey et al (2017), for 32 patients, the mean operative time was 50 (40-82) min, with the mean size of stones equivalent to our study 17 [5]. The operative time was linked with the location and size of the stones, according to Abdelhafez et al (2012), who studied the treatment by mini-PCNL with the mean size of stones of 36.7 ± 23.37 mm: In this case, the mean operative time was 99.2 ± 48.3 minutes [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Hennessey et al. [20] identified other advantages of MIP over both standard PCNL and RIRS. Firstly, patients' position was more flexible than RIRS and at least as equally flexible as standard PCNL.…”
Section: Currently Available Miniaturized Pcnl Techniquesmentioning
confidence: 98%
“…Combined, standard and mini tracts could be advised for staghorn, large burden or multiply located in the collecting system stones. In these cases, additional small tracts can improve anatomic approachability while decreasing renal trauma and bleeding and improving stone free rates [47] , [48] .…”
Section: Techniquesmentioning
confidence: 99%